Experimental investigation on fine particle emission during granite polishing process. Issue 9 (December 2015) - Saidi, M.; Songmene, V.; Kouam, J.; Bahloul, A.
Abstract Environmental, occupational health and safety regulations are pushing manufacturers towards reducing of manufacturing hazards including aerosol and fine particles. Granite shaping, cutting, and polishing are some of these processes producing large amount of dust containing silica that must be controlled. At the same time, the machining conditions must remain competitive and cost-effective and lead to quality parts. The goal of this work is to address these issues by determining the factors governing the dust emission during granite polishing in order to reduce the risk of exposition while producing quality parts. To do so, experimental polishing tests were carried on a vertical CNC machining center using an adaptable tool holder which controlled the contact pressure during the tests. Diamond polishing tools with different grit sizes were used. The workpiece tested were two granites, one with high silica content (white granite) and another with low silica content (black granite). The output responses studied include the surface finish, the forces, and the fine particle emission and dispersion. The experimental results led to establishing relationships between the surface finish, dust emission, and cutting forces on one hand and the abrasive sizes and polishing conditions on the other hand. It was found that the polishing tool grit size governs not only the granite surface finish but also the fine particle emission and the chip removal mechanism.